دور الإعلام الإسلامي في الرد على الإرهاب - عبادة، إبراهيم عبدالحليم (جامعة الزرقاء, 2015)
تهدف هذه الدراسة إلى استعراض بعض النماذج من التصورات المشوهة عن الإسلام من خلال الإعلام بالإضافة إلى إبراز دور الإعلام في مواجهة الإرهاب من خلال تصحيح الصورة الزائفة عن الإسلام. وقد انتظمت هذه الدراسة في ثلاثة مباحث: تناول أولها: مفهوم الإعلام والإعلام الإسلامي والإرهاب والمصطلحات المرادفة ، واستعرض الثاني منها : نماذج للتصورات المشوهة عن الإسلام من خلال الإعلام، وجاء الثالث منها: في دور الإعلام الإسلامي في مواجهة الإرهاب من خلال تصحيح الصورة ووضع الآليات المقترحة لمعالجة هذه الظاهرة. وقد خرجت هذه الدراسة بعدة نتائج من أهمها أن الإعلام الإسلامي لا يزال يعاني من ضعف في إيصال الصورة الحقيقية عن الإسلام بسبب سيطرة وتفوق الإعلام الغربي بالإضافة إلى محدودية الموارد المالية اللازمة لنشر الإسلام الصحيح منا توصلت الدراسة إلى وجود كثير من الإساءات الموجهة للإسلام والمسلمين من قبل الإعلام الغربي أدت إلى حالة من الكراهية وتغذية الفكر المتطرف، وقد أوصت هذه الدراسة بعدة توصيات من أهمها؛ توصية رئيسة تتعلق باقتراح إنشاء منظومة من القنوات الفضائية ذات الاهتمام الإسلامي البحث، التي تنشر صورة الإسلام الحقيقي، بعيدا عن التطرف أو التفريط، وتوصيات أخرى مثل: ضرورة رصد صورة الإسلام في الإعلام الغربي وذلك بمتابعة ما ينشر في وسائل الإعلام المختلفة حول المسلمين وقضاياهم ودينهم وتحليل محتواها ووضع التقارير اللازمة لها وعقد الندوات التي يمكن إن تسهم في معالجة هذا الأمر، كما أوصت بضرورة دعم العلاقة بين المؤسسات الإعلامية المختلفة وبين مؤسسات المجتمع المدني التي تعمل في مجال تصحيح ونشر الإسلام الصحيح والمعتدل وذلك حتى تتمكن من الرد وتصحيح الصورة الحقيقية عن الإسلام ومواجهة مؤسسات الإعلام الغربية التي تسئ إلى صورة الإسلام، وقد بين الباحث الجهات المناط بها تنفيذ هذه التوصيات، وآليات تنفيذها. The study aims to identify some models from the distorted perceptions of Islam by media and to highlight the role to face terrorism through correcting the distorted perceptions of Islam. The study divided into three chapters: First. Deals with the concept of Islam, Islamic media , terrorism and Synonymous terms. Second, deals with the models of distorted perceptions from Islam by media. Third deals with the role of Islamic media in face terrorism through correcting the perceptions and establishment suggestion tools to deals with this phenomena. The study concluded with many results; Islamic media still suffers from the weakness in transfer the correct fact of Islam due to western media control and its advanced, in addition to the limited financial resources necessary for spreading true Islam. The results of the study revealed that there is much of abuses against Islam and Muslims by the western media has led to a state of hatred and feeding extremist ideology. This study has been recommended by several of the most important recommendations; the basic recommendation related with suggestion to establish a system of satellite channels interest in Islamic search to spread the real image of Islam far from extremism or exaggeration. Another recommendations related with the need to monitor the image of Islam in the Western media through follow-up to what is published in various media about Muslims « their issues, their religion and analysis the content of this media content and puts reports that necessary for that. Seminars that can contribute to addressing this matter, as recommended by the need to support the relationship between the various media institutions and the institutions of civil society that working in the field of correcting and spreading the correct and moderate Islam, to be able to respond and correct the true image of Islam and face the Western media institutions that harm Islam. The researcher mentioned the authorized bodies entrusted in implementation these recommendation and the implementation mechanism.
Keywords: الإسلام -- الإعلام الإسلامي -- الإرهاب